Effect of a Coating Deposited on Foam Glass on the Ability to Absorb High-Frequency Electromagnetic Radiation; Glass and Ceramics; Vol. 75, iss. 5-6 - Kazmina O. V. Olga Viktorovna; Suslyaev V. I. Valentin Ivanovich; Dorozhkin K. V. Kirill Valerjevich; Kaymonov M. R. Maksim Ruslanovich; Stebeneva V. I. Valeriya Igorevna (2018, 2018)
Title screen